The analysis of race pacing in elite competitive long-distance speed skating - Takenaka, S.; Yuki, M.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to investigate the characteristics of racing pattern adopted by elite male speed skaters in official 5000m race. Twenty-four male skaters, who participated at the World Single Distances Speed Skating Championships 2008, were recorded using video camera (60Hz). The top group (top12 ranked skaters) was significantly faster than the 2nd group (13th to 24th ranked skaters) from 350m line to the finishing line (p<0.001~0.05). The variations of speed in curve sectors were smaller for the top group than the 2nd group (Lap2nd & 8th, p<0.05), and also smaller in straight sectors (Lap8th & 9th, p<0.01~0.05). These results suggest that it is important to adopt a "positive pacing strategy" and to distribute skating speed evenly as possible within each lap, especially not to decrease skating speed excessively in straight sectors at that time.